The Talent Industry Television, Cultural Intermediaries and New Digital Pathways - Boyle, Raymond (Springer International Publishing, 2018)
This book explores how the digital multiplatform delivery of television is affecting the role performed by cultural intermediaries responsible for talent identification and development. Drawing on original research from key stakeholders across the television and social video sectors such as broadcasters, commissioning editors and talent agents, it investigates whether the process of digitization is offering new pathways to capture and nurture a diverse talent base within the UK television industry. It also provides an in-depth study of how the term 'talent' has historically been interpreted and understood within the UK television industry through the BBC and commercial PSB's, such as ITV and Channel 4. The Talent Industry investigates how the traditional gatekeepers of talent in television are changing and examines the key role of talent agencies in managing and promoting contemporary on and off-screen talent in the digital age. .